Konsep Tanggung Jawab Serta Peranan Negara Terhadap Kesejahteraan Rakyat (Persepektif Hukum Internasional dan Ekonomi Islam) - Halimatul Maryani; Adawiyah Nasution (DE LEGA LATA: JURNAL ILMU HUKUM, 2018)
State is an organization that has territory, a gathering of people, government institutions and people's recognition to the state which aims to realize justice, provide legal certainty, provide order and security for the people (the people). This writing uses the normative juridical legal research method (normative research. The specification of the research in this paper is analytical descriptive research. The aim is to provide an overview, study, explain and analyze. The problem in this research is how the concept of responsibility and the role of the state towards the perspective of people's welfare from international law and Islamic economics, the Islamic view of state institutions or institutions cannot be separated from the integrated collective concept contained in the moral foundation and Islamic sharia provisions, for example the concept of brotherhood (ukhuwah), enlightenment (tausiah), leadership (khilafah) is the basis for the development of Islamic institutions in the form of the State, meaning religion is the basis or principle as a belief in the relationship of monotheism with Strength as the Creator (khaliq).